1997
DOI: 10.1111/j.1365-2494.1997.tb02349.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plant population density, composition and sward structure of a hill pasture during a pastoral fallow

Abstract: Appropriate pre-sowing methods for the introduc-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 18 publications
0
26
0
1
Order By: Relevance
“…Under deficit irrigation, grazing management should be based on species and growth habit and it is important to ensure that water soluble carbohydrate reserves are replenished after a grazing event to maximise persistence [94]. Pasture persistence may be improved by rotational grazing [106,107], leaving greater residual material following grazing, or by resting the pasture and limiting grazing to promote density and persistence [108].…”
Section: Grazing Management Of Water-stressed Pasturesmentioning
confidence: 99%
“…Under deficit irrigation, grazing management should be based on species and growth habit and it is important to ensure that water soluble carbohydrate reserves are replenished after a grazing event to maximise persistence [94]. Pasture persistence may be improved by rotational grazing [106,107], leaving greater residual material following grazing, or by resting the pasture and limiting grazing to promote density and persistence [108].…”
Section: Grazing Management Of Water-stressed Pasturesmentioning
confidence: 99%
“…No differences in chemical composition between the pastures have been found, but no detailed analysis of individual plant compounds (e.g., FA, secondary plant metabolites) has been reported. Pasture composition changes over the season (Walker et al, 2004) and the botanical composition of pastures with mixed swards is affected by varying responses of different species to grazing intervals, nutrient input, and herbage regrowth (Nie et al, 1997;Belesky et al, 1999). Differences in milk FA composition between seasons have been reported in various studies (Dunshea et al, 2008;Heck et al, 2009;Rutten et al, 2009).…”
Section: Effect Of Season and Stage Of Lactationmentioning
confidence: 99%
“…Barker et al (1991) found that the persistence of orchardgrass was improved under rotational grazing. A spell of grazing over summer and autumn promoted the plant population density and hence persistence of perennial grass-based pastures (Nie et al, 1997;Waller et al, 1999;Nie et al, 2005).…”
Section: Management and Persistencementioning
confidence: 99%